The direction of war : contemporary strategy in historical perspective - Strachan, Hew (Cambridge, United Kingdom : Cambridge University Press, 2013)
'The wars since 9/11, both in Iraq and Afghanistan, have generated frustration and an increasing sense of failure in the West. Much of the blame has been attributed to poor strategy. In both the United States and the United Kingdom, public enquiries and defence think tanks have detected a lack of consistent direction, of effective communication, and of governmental coordination'--
Includes bibliographical references and index.
Keywords: Strategy; Military history, Modern -- 21st century